How to do everything Macbook Air - Rich, Jason (New York McGraw-Hill Hill, 2012)
"How to do everything MacBook Air shows you how to harness the power of the new Mac OS X Mountain Lion operating system and use iTunes, iWork, iLife, iCloud, Safari, Contacts, Calendar, Reminders, Notification Center, Maril, and other powerful apps"--P. [4] of cover
Includes index
1
Keywords: Mac OS; MacBook (Computer); Macintosh (Computer)